2016
DOI: 10.1016/j.actbio.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical properties of strain-sensitive lyriform organs of a wandering spider (Cupiennius salei)

Abstract: Highly sensitive lyriform organs located on the legs of the wandering spider Cupiennius salei allow the spider to detect nanometer-scale strains in the exoskeleton resulting from locomotion or substrate vibrations. Morphological features of the lyriform organs result in their specialization and selective sensitivity to specific mechanical stimuli, which make them an interesting for bioinspired strain sensors. Here we utilize atomic force microscopy (AFM)-based force spectroscopy to probe nano-scale mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Fig. 1 shows the cover membrane of two lyriform organs: the vibration sensitive metatarsal lyriform organ (HS10) and the proprioreceptive tibial lyriform organ (HS8) [8] . The distal end of the lyriform organ of the metatarsus is a pad that cushions the joint between the metatarsus and tarsus.…”
Section: Slit Sensilla Of Arthropods (Spiders and Scorpions) 211 DImentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 1 shows the cover membrane of two lyriform organs: the vibration sensitive metatarsal lyriform organ (HS10) and the proprioreceptive tibial lyriform organ (HS8) [8] . The distal end of the lyriform organ of the metatarsus is a pad that cushions the joint between the metatarsus and tarsus.…”
Section: Slit Sensilla Of Arthropods (Spiders and Scorpions) 211 DImentioning
confidence: 99%
“…1e and 1f) [9] . It has also been found that the pad plays a key role in HS10 compression (stimulation), including large initial deformation caused by the tarsus (tens of µm) into smaller deformation (tens of nm) [8] .…”
Section: Slit Sensilla Of Arthropods (Spiders and Scorpions) 211 DImentioning
confidence: 99%
See 1 more Smart Citation
“…The dendrite branching of mechanosensory neuron needs to cover the area, setting the receptive field to encompass its sensory input . For the compound slit sensilla of spider, the attachment of the dendrite to the outer membrane covering each slit was visible externally and known as the coupling cylinder . Similarly, the dendrite terminal of H. petersii located in the vicinity of each slit tip shown a coupling cylinder ( Figure a–c and Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Yet in other species, Cupiennius salei , ablating the eyes has little effect on navigation (Barth & Seyfarth, 1971; Seyfarth & Barth, 1972). In these cases, numerous small slits located on the legs, known as lyriform organs, likely serve to provide air current or olfactory information that permits the animals to navigate in the absence of vision (Schmid, 2014; Wiegmann et al., 2019; Young et al., 2016). All the trials in our study were conducted under clear skies when sun compass and polarized light cues should have been available.…”
Section: Discussionmentioning
confidence: 99%